Representation of Women in the Film Marlina the Murderer in Four Acts: A Case Study Through Critical Discourse Analysis - Arnie Putri Rachmadhani; T. Thyrhaya Zein; Masdiana Lubis (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study discusses critical discourse analysis which aims to analyze the forms of gender discrimination and how women are represented in the film Marlina the murderer in four acts this study uses the Sara Mills model of discourse analysis by looking at the position of the subject-object and the position of the reader in the text. The research method uses descriptive qualitative, data collection with documentation studies with media content analysis. The results showed that the position of the subject was Marlina and Novi who described the position of men as objects. And the position of the object is Marlina and Novi. As objects, they are the result of the identification of the subject who describes them in their interpretation.